Pazopanib Maintenance Therapy in East Asian Women With Advanced Epithelial Ovarian Cancer: Results From AGO-OVAR16 and an East Asian Study. Issue 1 (January 2018) - Kim, Jae-Weon; Mahner, Sven; Wu, Ling-Ying; Shoji, Tadahiro; Kim, Byoung-Gie; Zhu, Jian-Qing; Takano, Tadao; Park, Sang-Yoon; Kong, Bei-Hua; Wu, Qiang; Wang, Kung-Liahng; Ngan, Hextan YS; et al.
Abstract : Objective: The recent phase 3 trial AGO-OVAR16 demonstrated that pazopanib maintenance improved median progression-free survival in patients with ovarian cancer whose disease did not progress during first-line treatment. However, this improvement was not seen in the subset of East Asian patients. The current analysis evaluated the efficacy and safety of pazopanib maintenance in East Asian patients from AGO-OVAR16 and a separate East Asian study. Materials and Methods: East Asian patients from AGO-OVAR16 (n = 209) and the East Asian study (N = 145) were randomized 1:1 to receive pazopanib 800 mg/d or placebo for up to 24 months. The primary end point for each study was progression-free survival by RECIST (Response Evaluation Criteria in Solid Tumors) based on investigator assessment. Clinical and genetics data were analyzed separately by study or pooled according to separate predetermined statistical plans. Results: Pazopanib maintenance had a detrimental effect on median progression-free survival versus placebo in East Asian patients from the combined studies (n = 354; 17.9 vs 21.5 months; hazard ratio, 1.114; 95% confidence interval, 0.818–1.518; P = 0.4928). Pazopanib maintenance showed a disadvantage in overall survival in East Asian patients from AGO-OVAR16 versus placebo (hazard ratio, 1.706; 95% confidence interval, 1.010–2.883; P = 0.0465); overall survival analysis was not performed in the East Asian study because of insufficient event numbers. Pazopanib-treated patients had a significantly higher incidence of grade 3 or higher hypertension (27%) and neutropenia (13%) versus placebo. Conclusions: The treatment effect of maintenance pazopanib in East Asian patients seemed to differ from that in non-Asian patients. In study-specific and pooled analyses, none of the potential factors analyzed could satisfactorily explain the different efficacy results of pazopanib in East Asian patients. Abstract : Supplemental digital content is available in the text.